Inventing Atlantic Canada : regionalism and the Maritime reaction to Newfoundland's entry into Canadian confederation - Slumkoski, Corey, 1972- (University of Toronto Press, 2011)
Inventing Atlantic Canada is the first book to analyse the reaction of the Maritime provinces to Newfoundland's entry into Confederation.